FEATURES OF THE DEVELOPMENT OF THE INTELLECTUAL POTENTIAL OF THE ENTERPRISE IN THE CONDITIONS OF SUSTAINABLE DEVELOPMENT - Паляниця, Станіслав (SWorldJournal, 2024)
Features of the development of the intellectual potential of the enterprise in the conditions of sustainable development include a number of key aspects. First, it is important to implement educational and training programs aimed at improving the qualifi